(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to evaluate the mathematics book for the first grade in the light of the objectives of the article. The study was limited to the teachers and teachers of the mathematics book for the first grade intermediate, who have a service of less than five years of graduates of faculties of education, the competence of the mathematics of the province of Baghdad for the academic year (2019 - 2020) and the number of (110) teachers and teachers in the province of Baghdad. The researcher used the descriptive approach and used the questionnaire as a tool for research, which includes (24) paragraphs divided into four areas (knowledge goals, goals related to mathematical skills, objectives related to thinking methods and problem solving, emotional goals). The results of the study showed that the field of knowledge objectives has the highest weighted mean (2.14) and a percentage weight (71.37). While the field of objectives related to methods of thinking and problem solving, less weighted mean (1.95), and a percentage weight (65,39). This result indicates a weakness in the field of goals related to methods of thinking and problem solving. The other areas ranged between (2,10 - 2.25) and their weights (70.17 - 75,30).